2019
DOI: 10.5539/ijef.v12n1p52
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between the Fama and French Three-Factor Model and the Fama and French Five-Factor Model: Evidence from the Egyptian Stock Market

Abstract: The focus of this paper is to test whether the Fama and French three-factor and five factor models can capture the variations of returns in the Egyptian stock market as one of the growing emerging markets over the time-period July 2005 to June 2016. To achieve this aim, following Fama and French (2015), the authors construct the Fama and French factors and three sets of test portfolios which are: 10 portfolios double-sorted on size and the BE/ME ratio, 10 portfolios double-sorted on size and operating profitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…The results indicate that the Fama and French three-factor model cannot explain excess stock returns in the EGX. These results contradict the findings of Shaker and Elgiziry (2014), Shaker and Abdeldayem (2018), and Ragab et al (2019), who supported the Fama and French three-factor model (1993) in the EGX. Our results do not support the Fama and French three-factor model (1993).…”
Section: Testing Herd Behaviourcontrasting
confidence: 96%
“…The results indicate that the Fama and French three-factor model cannot explain excess stock returns in the EGX. These results contradict the findings of Shaker and Elgiziry (2014), Shaker and Abdeldayem (2018), and Ragab et al (2019), who supported the Fama and French three-factor model (1993) in the EGX. Our results do not support the Fama and French three-factor model (1993).…”
Section: Testing Herd Behaviourcontrasting
confidence: 96%
“…Three sets of portfolios were used as test assets to find relationships between Egypt's stock market returns and size, the BE/ME ratio, operating profitability, and investments. Results reveal that the most significant effect is the size effect, and the five-factor model offers a complete explanation of the stock returns in the Egyptian stock market [9].…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, Li et.al [9] demonstrated the validity of the five-factor model on the U.S. stock market through their testing of a new pricing model. Furthermore, Ragab et.al [6] compared the Fama and French three-factor model and five-factor on the Egyptian stock market using time-series regression and the Gibbons Ross Shanken (GRS) test, and they revealed that the five-factor model provides a better explanation of stock returns in Egyptian Stock market based on the adjusted R2 and the values from the GRS test.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…After the empirical success of the Fama and French threefactor model, many researchers found additional patterns such as investment and profitability that are related to the average return stocks [6]. So Fama and French decided to incorporate the two factors profitability and investment into their previous threefactor model and developed a five-factor model.…”
Section: Fama and French Five-factir Modelmentioning
confidence: 99%
See 1 more Smart Citation